Hearing Dysfunction in Xpa-Deficient Mice - Shinomiya, Hitomi; Yamashita, Daisuke; Fujita, Takeshi; Nakano, Eiji; Inokuchi, Go; Hasegawa, Shingo; Otsuki, Naoki; Nishigori, Chikako; Nibu, Ken-ichi (Frontiers in Aging Neuroscience, 2017)
Xeroderma pigmentosum (XP) is a rare recessive heredity disease caused by DNA repair impairment characterized by photosensitivity and neurologic symptoms in half of the cases. There are eight subtypes of XP: XP-A–XP-G and XP variant. Among 8 subtypes, XP complementation group A (XP-A) display the lowest DNA repair ability and the severest cutaneous and neurologic symptoms. While its pathogenesis of skin symptoms have been well studied, that of neurological symptoms, including sensorineural hearing loss (SNHL) remains unknown. Basic studies have suggested that SNHL may be caused by inner ear damage, including damage to the spiral ganglion neurons and organ of Corti, and that the XP-A is associated with most severe form of SNHL in humans. Here, we report the occurrence of SNHL in Xpa-deficient mice. Xpa-deficient mice and wild-type mice underwent measurements for auditory brainstem response, and the results revealed that Xpa-deficient mice exhibited significantly greater (p<0.01) ABR thresholds at 4, 8 and 16 kHz than the wild-type mice. Furthermore, the number of spiral ganglion neurons was reduced in Xpa-deficient mice compared with that in wild-type mice, indicating that hearing loss may be related to spiral neuron deficiency, consistent with the few reports published in human patients with XP. These results provide important insights into the pathogenesis of SNHL in patients with XP-A.